The hidden side of Norwegian cabin fairytale: climate implications of multi-dwelling lifestyle. Issue 5 (19th October 2020) - Xue, Jin; Næss, Petter; Stefansdottir, Harpa; Steffansen, Rasmus; Richardson, Tim
ABSTRACT: In addition to a primary dwelling, having access to a non-primary dwelling for leisure activities is a mass phenomenon with a long tradition in Norway. This paper questions the Norwegian multi-dwelling lifestyle by critically discussing its climate implications. Based on a questionnaire survey and in-depth interviews with persons having access to non-primary dwellings, the paper analyzes the mobility pattern and housing consumption pattern of the multi-dwelling lifestyle. Two lifestyle groups are distinguished: traditional, and modern multi-dwelling lifestyles. A discussion of the climate implications of the two multi-dwelling lifestyles suggests that the traditional non-primary dwelling lifestyle is less climate harmful than the modern one. Furthermore, informed by the weak and strong sustainability perspectives, the paper suggests two climate policy pathways in order to raise and enrich the debates on climate-friendly development of the multi-dwelling lifestyle.